2014
DOI: 10.1136/jclinpath-2014-202367
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary pathologic manifestations of anti-glycyl-tRNA synthetase (anti-EJ)-related inflammatory myopathy

Abstract: Identifying ARS-associated autoantibodies in ILD patients with or without myopathy is desirable because patients may respond well to immunosuppressive therapy, and their prognosis is better than that of patients with idiopathic forms of DAD or UIP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 23 publications
1
16
1
Order By: Relevance
“…In most patients with EJ-ILD clinical disease behavior was reversible or progressive and irreversible disease. Although anti-EJ antibodies correlated well with ILD, there are a few reports which describe the clinical, radiological and pathological findings of EJ-ILD and no reports describe any detailed clinical courses [16, 26]. To our knowledge, this is the first study to describe the detailed clinical features of biopsy-proven EJ-ILD with long-term follow-up period.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In most patients with EJ-ILD clinical disease behavior was reversible or progressive and irreversible disease. Although anti-EJ antibodies correlated well with ILD, there are a few reports which describe the clinical, radiological and pathological findings of EJ-ILD and no reports describe any detailed clinical courses [16, 26]. To our knowledge, this is the first study to describe the detailed clinical features of biopsy-proven EJ-ILD with long-term follow-up period.…”
Section: Discussionmentioning
confidence: 92%
“…However, there are only a few reports describing the clinical features of patients with ILD with positive-anti-EJ antibody (EJ-ILD) [15, 16]. The aim of this retrospective study was to define the clinical, radiological and pathological features of patients with EJ-ILD with long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the prevalence of the non-Jo1 ARS group is higher in different cohorts such as patients labelled as 'idiopathic' IP, particularly in those with UIP and AIP (DAD) subtypes [27]. Data from several studies suggest that UIP and AIP are commonly seen in non-Jo1 ASS, in particular anti-EJ, anti-PL7 and anti-PL12 patients, where lung disease presents early in disease course and is the predominant manifestation [22,[27][28][29][30][31][32]. In a large series of Japanese patients positive for anti-Jo-1, anti-EJ, anti-PL-7, anti-PL-12, anti-KS or anti-OJ highlighted the degree of heterogeneity within ASS in terms of distribution and onset of myositis, lung disease and skin lesions [33].…”
Section: Anti-synthetase Syndromementioning
confidence: 99%
“…33,34 Overall, because the other anti-ARS antibodies make up less than 2% of patients with the antisynthetase syndrome, little is known about their specific phenotypes; however, smaller case series highlight the association of several of these less frequently observed anti-ARS antibodies with ILD. [35][36][37] Beyond these autoantibody specificities, anti-CADM-140/anti-MDA-5 antibodies are associated with a phenotype similar to the antisynthetase syndrome, with a high risk of rapidly progressive ILD. 38 Rarely found in other connective tissue disorders, anti-MDA-5 antibodies target interferon-induced helicase-1, a molecule that recognizes single-stranded RNA viruses as part of the innate immune response.…”
Section: Pulmonary Complications Of Inflammatory Myopathymentioning
confidence: 99%
“…5,52 Among patients with the antisynthetase syndrome, individual antibody specificity does not seem to correlate with histologic pattern, 21 although several studies have indicated a higher than expected prevalence of UIP and DAD compared with nonsynthetase subgroups. 33,35 Overall, these studies must be interpreted cautiously, because the estimated prevalence of histopathologic subtypes is influenced by specific serologically/clinically defined phenotypes as well as referral bias related to disease severity.…”
Section: Histopathologymentioning
confidence: 99%